Psychiatric medication and physical performance parameters – Are there implications for treatment? - Hirschbeck, Anna; Leao, Douglas Silva; Wagner, Elias; Hasan, Alkomiet; Roeh, Astrid (Frontiers in Psychiatry, 2022)
Abstract Introduction: The impact of psychiatric medications and their enhancing or impairing effects on physical performance remains inconclusive. Therefore, with this systematic review we provide a comprehensive overview of frequently used psychotropic drugs and their effects on physical performance for the purpose of providing empirical information and deriving prescription and therapy recommendations for clinical practice. Methods: We systematically searched PubMed, PsycInfo and Cochrane databases and extracted human studies investigating the effect of psychotropic drugs on parameters associated with the level of physical performance, such as exercise time, oxygen consumption, heart rate, muscle contraction or blood lactate concentration in physically healthy participants. 36 studies - comprising a broad range of psychotropic agents, such as antidepressants, antipsychotics, sedatives, and stimulants - were selected for final analyses. Results: Most studies (N=32) were randomized controlled trials (RCT) with a double-blind crossover design. Antidepressants (N=21) were the most frequently studied drug class, with contradictory results e.g. performance enhancement in warm environment but not in temperate conditions for bupropion or inconsistent findings between studies for other antidepressants. Antipsychotics (N=3) mainly showed impairing effects on physical performance, while stimulants (N=4) were often performance-enhancing. Sedatives (N=9) may cause a hangover effect. Conclusion: The examined studies with heterogeneous design showed different effects of psychiatric medications on physical performance. Antipsychotics seemed to be performance impairing, while the findings for antidepressants and sedatives were more inconsistent. Stimulants were the only group with consistent performance-enhancing effects. However, most studies were conducted with a small sample size (N<10), mostly in well-trained subjects rather than in patients with psychiatric disorders, and most studies used single-dose designs. These issues impede the formulation of generalized conclusions for treatment regimes and should therefore be considered in further longitudinal studies for clinically reliable statements. Nevertheless, answering our research question is quite relevant for clinical practice and therapeutic prescription and should be further investigated especially considering the high drop-out rates in drug treatment.